2022
DOI: 10.3390/biomedicines10020296
|View full text |Cite
|
Sign up to set email alerts
|

An Early Th1 Response Is a Key Factor for a Favorable COVID-19 Evolution

Abstract: The Th1/Th2 balance plays a crucial role in the progression of different pathologies and is a determining factor in the evolution of infectious diseases. This work has aimed to evaluate the early, or on diagnosis, T-cell compartment response, T-helper subsets and anti-SARS-CoV-2 antibody specificity in COVID-19 patients and to classify them according to evolution based on infection severity. A unicenter, randomized group of 146 COVID-19 patients was divided into four groups in accordance with the most critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 82 publications
3
26
0
Order By: Relevance
“… 126 , 127 Severe COVID‐19, in turn, provokes dampened Th1 and Treg responses, while promoting the Th17 profile. 128 , 129 , 130 Similar to obesity, the IL‐17/IL‐10 ratio is increased in COVID‐19 cases, even in deceased patients, as compared to those who improved. 130 The cytokine milieu in these changes plays an important role.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 126 , 127 Severe COVID‐19, in turn, provokes dampened Th1 and Treg responses, while promoting the Th17 profile. 128 , 129 , 130 Similar to obesity, the IL‐17/IL‐10 ratio is increased in COVID‐19 cases, even in deceased patients, as compared to those who improved. 130 The cytokine milieu in these changes plays an important role.…”
Section: Discussionmentioning
confidence: 98%
“…The Treg/Th17 ratio is decreased in obesity, and this is related to metabolic health 126,127 . Severe COVID‐19, in turn, provokes dampened Th1 and Treg responses, while promoting the Th17 profile 128–130 . Similar to obesity, the IL‐17/IL‐10 ratio is increased in COVID‐19 cases, even in deceased patients, as compared to those who improved 130 .…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, NK cell depletion leads to reduced Th1 responses [ 63 ]. Our group recently described the importance of a strong Th1 response for a positive outcome of COVID-19 [ 14 ]. This fact together with the findings described in this work suggests that adequate NK activity, both as an effector and modulator towards the Th1 response, would be essential to establish a coordinated cytotoxic response of innate and adaptive immunity, which allows for the prompt clearance of SARS-CoV2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…One possible hypothesis is that immune dysregulation is associated with the presence of comorbidities and with the predominant immune response in the initial moments of the disease [ 12 ]. It has been observed that rapid Th1 responses are associated with lower probabilities for the development of hyperinflammatory complications, which are frequently observed in patients with an initial Th2 and/or Th17 immune response [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Asymptomatic SARS-CoV-2 infected individuals showed a potent and robust Type 1 immunity with high CD8 + T cell count, having a lower count of Th17 cells [19] . Conversely, severe COVID-19 patients presented with Th17-skewed immunity, fewer Type 1 responses and more antigen experienced T-cells.…”
mentioning
confidence: 99%